Avaliação em larga escala e trabalho docente: um estudo de caso sobre os desdobramentos do PAEBES, em uma escola estadual do Espírito Santo - Avanci, Roberta Aparecida (2024)
This dissertation, developed within the Graduate Program in Teaching, Basic Education, and Teacher Training at the Federal University of Espírito Santo (UFES), and linked to the research line "School Practice, Teaching, Society, and Teacher Training," aimed to analyze the influences of PAEBES (Programa de Avaliação da Educação Básica do Espírito Santo) on the work of teachers in a high school located in southern Espírito Santo. The methodology used is based on the theoretical methodological assumptions of Historical and Dialectical Materialism and adopts a case study approach. Data were collected through documentary consultation, participatory observation recorded in a field journal, and semi-structured interviews with four high school teachers, one from each area of knowledge. For data analysis, the focus of Historical and Dialectical Materialism was also applied. The analysis was supported by discussions on neoliberalism and its implications for education over recent decades, exerting strong control over educational systems. Regarding evaluations and teaching work, particularly PAEBES, the study revealed how these evaluations influence the work of teachers at the state school where the research was conducted. Specifically, it observed influences such as the restriction of teacher autonomy, curriculum narrowing, the implementation of performance bonuses, the focus on student training activities, and the responsibility and subjectivity placed on teachers.